2006
DOI: 10.1128/aem.72.2.1459-1466.2006
|View full text |Cite
|
Sign up to set email alerts
|

Production of the Lantibiotic Salivaricin A and Its Variants by Oral Streptococci and Use of a Specific Induction Assay To Detect Their Presence in Human Saliva

Abstract: Salivaricin A (SalA), the first Streptococcus salivarius lantibiotic to be characterized, appears to be inhibitory to most Streptococcus pyogenes strains. A variant of the SalA structural gene (salA1) is present in more than 90% of S. pyogenes strains, but only strains of M serotype 4 and T pattern 4 produce the biologically active peptide. The present study identifies four additional variants (salA2 to salA5) of the SalA structural gene and demonstrates that each of the corresponding inhibitory peptides (SalA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 24 publications
2
123
0
4
Order By: Relevance
“…In some concentrations, lantibiotic production is triggered [11]. According to Wescombe et al [8], salivaricin A production can be detected in individuals' saliva in varying concentrations because there is a variety of salivary flow rates that dissolve salivaricin A and allow adsorption in normal cell flora [8]. SDS-PAGE results in the current study showed that from six S. salivarius samples, only four subjects produced protein with the same profiles, containing one band located inline.…”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…In some concentrations, lantibiotic production is triggered [11]. According to Wescombe et al [8], salivaricin A production can be detected in individuals' saliva in varying concentrations because there is a variety of salivary flow rates that dissolve salivaricin A and allow adsorption in normal cell flora [8]. SDS-PAGE results in the current study showed that from six S. salivarius samples, only four subjects produced protein with the same profiles, containing one band located inline.…”
Section: Resultssupporting
confidence: 46%
“…A centrifuge tube (15 ml, 50 ml), cytobrush, 1000 ml tipped pipet, 200 ml tipped pipet, micropipette, Eppendorf tube, sterilized reaction tubes, 96-well microplate, incubator, anaerobic jar, vortex, mini centrifuge, autoclave, centrifuge, orbital shaker, enzyme-linked immunosorbent assay plater reader, analytic scale, water bath, round end ose berujung bulat, light lamp, Petri dishes, thermal cycler T100, electrophoresis, Gel Doc, Thermoblock, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) chamber, SDS-PAGE tank, and AxioCam ERc5s (Zeiss) microscope were the tools used to conduct this study. Additional materials included a brain-heart infusion (BHI) broth, BHI agar, sabouraud dextrose agar, bakto agar (Biomatic), mitis salivarius agar (MSA), sterilized aquadest, aquabides, cotton, aluminum foil, 70% alcohol, gas mixture (N 2 , CO 2 : 10%; H 2 : 10%), phosphate buffer saline, primer Sal-AUS (5'-GTAGAAAATATTTACTACATACT) [8], primer Sal-ADS (5'-GTTAAAGTATTCGTAAAACTGATG) [8], nucleus-free water, Dream Taq, Agarose, gel red, Tris-acetate-ethylenediaminetetraacetic acid buffer, 100 bp ladder, 10 mM Tris-HCl pH 7.4 liquid, 0.1 M Tris-HCL pH 6.8 liquid, phenyl methyl sulfonyl fluoride, glycerol, Coomassie brilliant blue, albumin protein standard, acrylamide 40%, stacking gel buffer, resolving gel buffer, SDS 10%, ammonium persulfate, tetra methyl ethylene diamine, marker protein (Peqlab), MiliQ water, Laemmli buffer, β-mercaptoethanol, SDS running buffer, C. albicans ATCC 10231 glycerol stocks, and S. salivarius ATCC 13419 glycerol stocks.…”
Section: Methodsmentioning
confidence: 99%
“…Then, E. faecalis were dissolved and incubated for 24 hrs. After that, the formed inhibition zone was measured [12].…”
Section: Identification Methods Of S Salivariusmentioning
confidence: 99%
“…Identification of colony morphology was conducted by observing the size and consistency of the surface (big, soft, smooth, and mucous-like colony that looks like a gum drop) [12]. Colonies considered as S. salivarius were taken and confirmed using the polymerase chain reaction (PCR) technique with SalAUS primers (5'-GTAGAAAATATTTACTACATACT) and SalADS (5'-GTTAAAGTATTCGTAAAACTGATG) [13]. PCR amplification results were analyzed using 1% agarose running on electrophoresis for 30 minutes (100V) [13].…”
Section: Ptmds 2017 | the 1st Physics And Technologies In Medicine Anmentioning
confidence: 99%
“…Colonies considered as S. salivarius were taken and confirmed using the polymerase chain reaction (PCR) technique with SalAUS primers (5'-GTAGAAAATATTTACTACATACT) and SalADS (5'-GTTAAAGTATTCGTAAAACTGATG) [13]. PCR amplification results were analyzed using 1% agarose running on electrophoresis for 30 minutes (100V) [13]. DNA strands that were 118 bp indicated that the colonies identified on the MSA medium were S. salivarius.…”
Section: Ptmds 2017 | the 1st Physics And Technologies In Medicine Anmentioning
confidence: 99%